2018
DOI: 10.1016/j.jbef.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

On the neural substrates of the disposition effect and return performance

Abstract: We experimentally assess the disposition effect and return performance, using electroencephalogram to measure the brain activity of the participants. The design of the experiment follows a previous protocol (Frydman et al., 2014). Our sample was made up of 12 undergraduates (all male, age range 18 to 29, mean age 22.2) and five professional stock traders (all male, age range 21 to 37, mean age 30.2). We find neural support for the finding that professionals are more likely to escape the disposition effect . We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Here we detail Odean’s metric [11] following our own presentation published elsewhere [2]. In a given period of time, each stock is assigned to one of four categories: 1) as a gain realized, whenever a stock is sold at a price that is higher than the average purchase price; 2) as a loss realized, whenever it is sold at a price that is lower than the average purchase price; 3) as a paper gain, whenever its price is higher than its average purchase price, but the stock is not sold during that period; and 4), as a paper loss, whenever its price is lower than its average purchase price, but the stock is not sold during the period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we detail Odean’s metric [11] following our own presentation published elsewhere [2]. In a given period of time, each stock is assigned to one of four categories: 1) as a gain realized, whenever a stock is sold at a price that is higher than the average purchase price; 2) as a loss realized, whenever it is sold at a price that is lower than the average purchase price; 3) as a paper gain, whenever its price is higher than its average purchase price, but the stock is not sold during that period; and 4), as a paper loss, whenever its price is lower than its average purchase price, but the stock is not sold during the period.…”
Section: Methodsmentioning
confidence: 99%
“…The disposition effect is one of the most studied behavioral biases in finance [1]. Many explanations have been proposed but none is established [2] [3]. One particular aspect of interest in our study of the phenomenon is investor experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different kinds of investors have different disposition effect. Dorow and Jr (2018) [8] tested the changes of neurological status through experiment, found that both professional investors and non-professional investors have disposition effect, but the professional investors is smaller than the non-professionals. Choe and Eom (2010) [11] get same results, by empirical analysis about Korean Futures Market.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism driving the disposition effect has recently been documented through simulation and pays particular attention to the influence of different risk preferences, as suggested by prospect theory, together with a preference for immediate rewards over delayed rewards (Shoji & Kanehiro, 2016). Very recently, Dorow, Costa, Takase, Prates, and Silva (2018) have shown that there is a change in brain activity of the participant in the process of the disposition effect and return performance. Recent reports have discussed the variation of disposition effect based on market state and divided the market into "bull" or "bear" market states, arguing that the disposition effect may vary based on market state (Muhl & Talpsepp, 2018).…”
Section: Introductionmentioning
confidence: 99%